Web and Mobile Data Management System for Garongan Asri Garbage Bank: A Case Study - Nurfaldini, Shofi Isnaeni; Aji, Adam Sekti (Universitas Bina Darma, 2023)
This research addresses the inefficiencies of manual garbage data management by developing a dual-platform system: a website-based application for Garongan Asri Garbage Bank staff and a mobile application for customers. Utilizing the waterfall method for systematic development, the project involved stages of analysis, design, coding, testing, support, and maintenance. Key technologies used include the Bootstrap framework, Visual Studio Code, Android Studio, and MySQL database. The resulting website application enables staff to efficiently manage garbage data, while the mobile app allows customers to access their disposal history. The effectiveness of these applications was confirmed through black box testing, demonstrating their functionality and suitability for improving garbage data management and customer service.